Emerging technologies in wireless ad-hoc networks : applications and future development - Aquino Santos, Raul, 1965-; Rangel Licea, Victor, 1972-; Block, Arthur Edwards, 1957- (Hershey, PA ; New York : Information Science Reference, 2011)
"This book provides the rationale, state-of-the-art studies and practical applications, proof-of-concepts, experimental studies, and future development on the use of emerging technologies in wireless ad-hoc networks"--
Includes bibliographical references and index.
Keywords: Ad hoc networks (Computer networks)